Green Strategy – Halal Branding Management as a Solution to Increase the Economic Growth of MSMES - IMANINGSIH, Erna Soriana; RAMLI, Yanto; OKTAVIANI, Dea (Indonesia Strategic Sustainability, 2024)
The UMB team implemented PKM in partnership with MSME actors in Kranggan Village in Kademangan Village, Tangsel City. Attended by 36 MSME players in the culinary sector. The mainstay products of these MSME players are roasted peanuts, ketapang seeds, banana chips, kembang goyang, and other types of chips. The problems experienced by partners are as follows: there are several superior products produced by culinary MSMEs in Kranggan Village, namely the production of roasted peanuts which is experiencing sluggish development. The main obstacle is mainly caused by the need for knowledge by MSME players about the importance of marketing strategies, especially branding strategies, to increase the added value of products and make their uniqueness known to consumers. The solutions offered are: 1) Providing training regarding marketing and export strategies for roasted peanut products to reach domestic markets and export to Middle Eastern countries. 2) Providing training related to Branding Management Strategy by providing product brands and green halal brand certification as product identities to encourage economic growth for MSMES.